Factors, which condition the effectiveness of qualified female volleyball players physical actions - Tinyukov, A. B.; Avramova, N. V. (The Russian Journal of Physical Education and Sport, 2016)
Annotation. The perspective directions of sports training effectiveness increase among volleyball players are the following: the character setting of physical readiness and the technique of the attacking blow fulfillment interconnection; the optimal parameters of the individual training loads search; estimation criteria of their volume and intensity creation. Competitive activity effectiveness of qualified volleyball players is determined by different pedagogical conditions and factors, among which it is important to reveal the most important ones, the use of which helps to improve physical and technical readiness level of the players. Research methods: scientific-methodical literature analysis and summarizing, pedagogical experiment, testing,statistical data manipulation. Materials. The article is about the factors, which influence greatly the effectiveness of technical-tactical actions, determining the improvement of qualified volleyball players` sportsmanship. Results. Created on the basis of these factors methodology of technical-tactical readiness improvement among players showed the prospectivity of this approach. Such kind of factors as the skills formation of spatio-temporal orientation in case of interaction with the partners and opponents, physical actions extrapolation and the character of the opponent`s motor acts prediction reflect greatly the level of volleyball players` sportsmanship. It conditions the necessity to choose the most effective motional tasks, the fulfillment of which provides these skills formation, attention concentration on the weak points of the players` physical and technical readiness revelation and it helps to change the content of the training lessons. Conclusion. The results of the pedagogical experiment showed the prospectivity of is physical and technical readiness development direction among qualified volleyball players; the importance of motional tasks choice system, which provide the set aim achievement, the realization of which proves many-sided readiness of the players. The degree of these skills formation provides the diversity increase of the ways to fulfill the set motional task and it considerably enriches their motional skills, which is an important condition for sportsmanship improvement.